2014
DOI: 10.1016/j.scr.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Heterelogous expression of mutated HLA-G decreases immunogenicity of human embryonic stem cells and their epidermal derivatives

Abstract: Human embryonic stem cells (hESCs) are capable of extensive self-renewal and expansion and can differentiate into any somatic tissue, making them useful for regenerative medicine applications. Allogeneic transplantation of hESC-derived tissues from results in immunological rejection absent adjunctive immunosuppression. The goal of our study was to generate a universal pluripotent stem cell source by nucleofecting a mutated human leukocyte antigen G (mHLA-G) gene into hESCs using the PiggyBac transposon. We suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 68 publications
(62 reference statements)
0
25
0
Order By: Relevance
“…However, according to the 'missingself theory', MHC class I-deficient mouse and human PSCs become susceptible to NK cell killing [23][24][25] . Although isolated expression of HLA-E 26 or HLA-G 27 in human pluripotent stem cells has been used to mitigate NK cell cytotoxicity, we observed that CD47 is a very effective non-MHC ligand to silence all innate immune responses. However, cells eluding immune monitoring may pose the long-term risks of uncontrollable malignant transformation or impaired virus clearance, although for the latter alternative mechanisms have been shown 28 .…”
mentioning
confidence: 88%
“…However, according to the 'missingself theory', MHC class I-deficient mouse and human PSCs become susceptible to NK cell killing [23][24][25] . Although isolated expression of HLA-E 26 or HLA-G 27 in human pluripotent stem cells has been used to mitigate NK cell cytotoxicity, we observed that CD47 is a very effective non-MHC ligand to silence all innate immune responses. However, cells eluding immune monitoring may pose the long-term risks of uncontrollable malignant transformation or impaired virus clearance, although for the latter alternative mechanisms have been shown 28 .…”
mentioning
confidence: 88%
“…C) . Such protection has also been demonstrated in hESCs ectopically expressing an optimized form of HLA‐G .…”
Section: Generation Of Uc‐hescs To Prevent Immune Rejectionmentioning
confidence: 77%
“…Since 2013, breakthroughs in genome editing in hPSCs have made it possible to knock out HLA and genes essential for HLA expression, including β ‐2‐microglobulin ( B2M ) for class‐I HLA and class‐II MHC transactivator ( CIITA ) for class‐II HLA expression. In addition, hypoimmunogenic hESCs can be obtained by knocking down B2M or ectopically expressing a modified form of HLA‐G . Recently, it was reported that UC‐hESCs can also be achieved through the disruption of T cell costimulatory pathways with cytotoxic T lymphocyte antigen 4 fused with immunoglobulin (CTLA4‐Ig) and simultaneous activation of the T cell inhibitory pathway with programmed death ligand‐1 (PD‐L1) .…”
Section: Generation Of Uc‐hescs To Prevent Immune Rejectionmentioning
confidence: 99%
“…cell killing [23][24][25] . Although isolated expression of HLA-E 26 or HLA-G 27 in human pluripotent stem cells has been used to mitigate NK cell cytotoxicity, we observed that CD47 is a very effective non-MHC ligand to silence all innate immune responses. However, cells eluding immune monitoring may pose the long-term risks of uncontrollable malignant transformation or impaired virus clearance, although for the latter alternative mechanisms have been shown 28 .…”
mentioning
confidence: 86%